Challenges and Prospects of Utilizing Natural Resources of Nepal For Sustainable Development - Khadka, Bhesh Bahadur; Shekhar, Chandra (A Bi-annual South Asian Journal of Research & Innovation, 2025)
One prominent challenge is the socioeconomic disparity prevalent in the country. As natural resources are often concentrated in specific regions, ensuring that development initiatives align with local values and aspirations. Environmental degradation poses other formidable challenges, agricultural practices contribute to ecological imbalance. A sociological lens helps unravel the intricate web of human– environment interactions, exploring how societal norms and behaviors impact the environment and in turn, affect the sustainability of natural resources. Amidst these challenges, the study also uncovers abstracts or innovative approaches that hold promise for sustainable development. Collaborative community-based models, incorporating local knowledge and fostering social cohesion, emerge as potential solutions. Moreover, promoting education and awareness of sustainable practices can empower communities to actively participate in resource management. The role of social science. Sociology is one of the vacuumed spaces which is zero. The sociology component of social phenomena is wide of the ranch. Studying sociology is different from other subjects. Law of sociology also starts from zero and reaches zero value Barren land and mining resources. Control outgoing skilled youth force and follow Human science: Human civilization called human science is the center of sociology. Apart from humans, other animals also have their kind of society. For that reason, this study concludes that it is necessary to use natural resources for the development of sociology related to this study.